Sovereign Risk, Currency Risk, and Corporate Balance Sheets - Du, Wenxin; Schreger, Jesse (Review of Financial Studies, 2022)
Abstract We provide a comprehensive account of the evolution of the currency composition of sovereign and corporate external borrowing by emerging markets from 2003 to 2017. We show that a higher reliance on foreign currency debt by the corporate sector is associated with higher sovereign default risk. We introduce local currency sovereign debt and private sector currency mismatch into a standard sovereign debt model to examine how the currency composition of corporate borrowing affects the sovereign’s incentive to inflate or default. A calibration of the model generates the empirical patterns of sovereign credit risk.